SIMULATION OF NO2 DISTRIBUTION IN INDUSTRIAL ESTATE AREA ON WESTERN MONSOON SEASON USING CALPUFF MODELLING - Nurushahifa, Avia
According to the 2011 BLHK Cilegon Environmental Impact Analysis report in the Industrial Estate area in West Java, wind direction and speed are affected by the Western Monsoon Wind in December, January, February with the dominant wind direction coming from the west. The west monsoon wind movement in the Industrial Estate will bring NO2 gas to the settlement. This study determined the western monsoon wind days with three categories, namely weak western monsoon wind day, moderate western monsoon wind day, and strong western monsoon wind day using ECMWF wind data at 500mb. Then, analyzed winds at various heights using CALMET output windroses with input WRF models. Simulation of the distribution of NO2 gas in Industrial Estates uses the CALPUFF model using topographic data, landuse data, emission data and using CALMET output wind fields. The results of this study indicate that on three days of observation, the dominant wind movement at 1000 meters wind blew from the west, at 120 meters and 10 meters wind blew 45o from the southwest or northwest when the west monsoon wind was weak and moderate then from the west when the west monsoon wind is strong. The distribution of NO2 gas in the three categories of days is mostly towards to the east, with the furthest distribution occurring when the west monsoon wind is moderate and strong. The distribution pattern of NO2 gas has wider land coverage at night than during the day. The results of the observation state that there is no overforecasting from the output of the CALPUFF model.